Development of an inquiry-based module with scientific equipment to facilitate primary school students learning the force concept - Herwinarso; Koswojo, Jane; Pratidhina, Elisabeth (Journal of Education and e-Learning Research, 2023)
Recently, science, technology, engineering and mathematics (STEM) applications have become more demanding, promoting students' interest in science from an early age. Science class in primary school needs more attention to attract students’ interest. This study aims to develop an inquiry- based module with scientific equipment for the primary school level to optimize science learning at the primary school level. The development process used a 4-D (define, design, develop and disseminate) model. The developed module and equipment cover the topics of forces and include four experiments, i.e., exploring friction in inclined planes, exploring the mechanical advantage of a pulley, observing magnetic force and exploring static equilibrium in a lever. The modules and scientific equipment are distributed to some schools in Indonesia that lack practical work facilities. The inquiry-based modules and scientific equipment are implemented in classes at four primary schools in Indonesia. In this study, the students' response to the implementation of inquiry-based modules and scientific equipment in the class is also investigated. Overall, the average of the students' responses is 3.37 (out of 4.00). It means students respond positively to the learning activity and the supporting module. Active learning with an inquiry approach is feasible to attract students' interest in science.